Sink or Source: Alternative Roles of Glacier Foreland Meadow Soils in Methane Emission Is Regulated by Glacier Melting on the Tibetan Plateau - Xing, Tingting; Liu, Pengfei; Ji, Mukan; Deng, Yongcui; Liu, Keshao; Wang, Wenqiang; Liu, Yongqin (Frontiers in Microbiology, 2022)
Glacier foreland soils have long been considered as methane sinks. However, they are flooded by glacial meltwater annually during the glacier melting season, altering their redox potential. The impacts of this annual flooding on methane emission dynamics and methane-cycling microorganisms are not well understood. Herein, we measured in situ methane flux in glacier foreland soils during the pre-melting and melting seasons on the Tibetan Plateau. In addition, high-throughput sequencing and qPCR were used to investigate the diversity, taxonomic composition, and the abundance of methanogenic archaea and methanotrophic bacteria. Our results showed that the methane flux ranged from -10.11 to 4.81 μg·m-2·h-1 in the pre-melting season, and increased to 7.48 to 22.57 μg·m-2·h-1 in the melting season. This indicates that glacier foreland soils change from a methane sink to a methane source under the impact of glacial meltwater. The extent of methane flux depends on methane production and oxidation conducted by methanogens and methanotrophs. Among all the environmental factors, pH (but not moisture) is dominant for methanogens while both pH and moisture are not that strong for methanotrophs. The dominant methanotrophs were Methylobacter and Methylocystis, whereas the methanogens were dominated by methylotrophic Methanomassiliicoccales and hydrogenotrophic Methanomicrobiales. Their distributions were also affected by microtopography and environmental factor differences. This study reveals an alternative role of glacier foreland meadow soils as both methane sink and source, which is regulated by the annual glacial melt. This suggests enhanced glacial retreat may positively feedback global warming by increasing methane emission in glacier foreland soils in the context of climate change.